YouTube To Improve Student’s Speaking English Skill - Mainike Silvi Rety Badian (CV. Kalimasada Group Profesional, 2023)
English has become an international language, so the mastery of English language skills is important. However, the students still face some problems that make them unmotivated and hinder speaking. Considering these situations and conditions, the teacher must address this challenge and determine the most effective strategy for involving students in the teaching and learning process, particularly in speaking. As a result, YouTube is selected as one of the options for teaching speaking in this article in order to determine how using YouTube to improve students' speaking skills. To find out the use of YouTube video to improve student’s speaking skill, a qualitative approach was used in this research. Qualitative research was utilized to conduct this research. To collect the data for the study, a questionnaire using Google Forms with close-ended questions was utilized. The questionnaire will contain 5 questions that were based on previous research regarding the roles of YouTube in improving English speaking skills. After implementing the action of research, the researcher found that the use of YouTube video in the teaching speaking had enhanced and motivated the students’ speaking English skill.